2009
DOI: 10.1007/s10534-009-9249-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary selenium supplementation on cadmium absorption and retention in suckling rats

Abstract: Selenium (Se) reduces cadmium (Cd) toxicity in adult animals, but its effects in newborn animals are still unknown. This study investigated Cd (as CdCl2) absorption, distribution, and retention in suckling rats receiving oral Se supplementation (as Na2SeO3) in equimolar doses (8 μmol Cd and/or Se per kg b.w./day). Selenium was given either before and during Cd exposure (Sepre + Cd group; pretreatment group) or only during Cd exposure (Se + Cd group). Rats were treated from postnatal day (PND) 6-14 as follows: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 70 publications
(81 reference statements)
3
25
1
5
Order By: Relevance
“…Direct comparison with inorganic Se cannot be made in the present study as it was not used; however, previous work with inorganic Se showed that 0.1 mg/kg Se, as Na 2 SeO 3 , added to diets contained 200 mg/kg of CdCl 2 did not induce any significant changes in the levels of Cd accumulation in rats' kidney, liver (Jihen et al, 2008) and testis (Messaoudi et al, 2010). However, another study showed that inorganic Se supplementation reduced Cd levels in the liver and kidney of rat pups (Lazarus et al, 2009). It is possible that differences regarding reduction or not of Cd accumulation by Se noted between different studies may be related with the administered doses, the mode of application and the duration of exposure.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Direct comparison with inorganic Se cannot be made in the present study as it was not used; however, previous work with inorganic Se showed that 0.1 mg/kg Se, as Na 2 SeO 3 , added to diets contained 200 mg/kg of CdCl 2 did not induce any significant changes in the levels of Cd accumulation in rats' kidney, liver (Jihen et al, 2008) and testis (Messaoudi et al, 2010). However, another study showed that inorganic Se supplementation reduced Cd levels in the liver and kidney of rat pups (Lazarus et al, 2009). It is possible that differences regarding reduction or not of Cd accumulation by Se noted between different studies may be related with the administered doses, the mode of application and the duration of exposure.…”
Section: Discussioncontrasting
confidence: 52%
“…The majority of studies examining ways to reduce Cd toxicity with Se were conducted in mammals using inorganic Se (Jihen et al, 2008;Messaoudi et al, 2010). Inorganic Se orally administered to suckling rats, equimolar to Cd, reduced Cd levels in the liver and kidney of the pups (Lazarus et al, 2009). Moreover, organic Se is a highly available form of Se for livestock and provides antioxidant protection at a level greater than inorganic Se (Mahan, 1999;Mahmoud and Edens, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Se is incorporated into proteins to develop selenoproteins, some of which are important antioxidant enzymes, such as glutathione peroxidase (GPx), the enzyme playing central role in antioxidative response of the animal organism. Lazarus et al (2009) observed the effect of Se supplementation of the Cd-exposed suckling rats on GPx activity in brain and kidney of animals. Although not proven by the measurement of the enzymatic activity in this experiment, the engagement of the Se-incorporating enzymes is expectable in this case.…”
Section: Resultsmentioning
confidence: 99%
“…Special attention was paid to the Se interaction with toxic elements, especially Cd. Sasakura and Suzuki (1998) proved complexation mechanisms of Cd with selenoprotein P. Lazarus et al (2009) showed a more substantial decrease in blood Cd and Se in rats exposed to both elements compared to those exposed to them individually. In the rat liver, Cd accumulation decreased in Se-supplemented animals compared to the rats exposed solely to Cd, as well.…”
Section: Introductionmentioning
confidence: 93%
“…Перспективним в цьому напрямку є вирощування рослин-накопичувачів Кадмію з метою зниження його рівня в грунті (Grant et аl., 2008). Експериментально було доведено, що здатність до виведення важких металів (у тому числі й кадмію) з тваринного організму мають Селен (El-Sharaky et al, 2007;Lazarus et al, 2009;Pirova et al, 2010), Цинк та Залізо (Alonco et al, 2004), глиноземи та алюмосилікати (Zasekin et al, 2000;Beltcheva et al, 2015), пектиновмісні добавки (Jourdain, 2005;Tarasenko et al, 2006) тощо. Заслуговує також на увагу застосування в годівлі тварин «функціональних кормів» (Banchi et.…”
unclassified